Sorghum recovery and immobilization of 15N labeled urea-N as affected by sewage sludge co-application - kchaou, Rajia; KHELIL, Mohamed Naceur; REJEB, Saloua; HENCHI, Belgacem; DESTAIN, Jean Pierre (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
A pot experiment was conducted to assess the fate and recovery of urea-N applied to sorghum (Sorghum sudanense) both in the presence and in the absence of sewage sludge. For a better understanding of the interaction between urea N and N originating from sewage sludge, 15N isotope technique was used. 15N-labeled urea was added to soil at 0, 60, 100 kg N.ha-1, and unlabeled sewage sludge was added at 0 and 45 kg N.ha-1. In the absence of sewage sludge, 15N recovery (15NR) was 34% of the 15N- Urea applied at 60 kg N.ha-1. It increased to 55% as the urea N rate increased to 100 kg N.ha-1. Co-application of sewage sludge with the highest dose of urea led to a decrease of urea 15NR by 11% as compared to that in the absence of sewage sludge. Application of sewage sludge significantly improved the immobilization of urea-derived N in soil, from 13 to 42 % and from 24 to 31% of 60 and 100 kg N urea applied respectively. Thus, sewage sludge ensured prolonged and continued availability of fertilizer N to plants thereby leading to reduce N loss and to higher fertilizer use efficiency.